The Anatomy of U.S. Sick Leave Schemes: Evidence from Public School Teachers - Cronin, Christopher J.; Harris, Matthew C.; Ziebarth, Nicolas R. (The Review of Economics and Statistics, 2026)
Abstract We study how public school teachers use paid sick leave. Most US sick leave schemes operate as individualized credit accounts: Paid leave is earned, and unused leave accumulates. We construct a unique dataset of daily leave balances and behavior among 982 teachers for 2010–2018. Sick leave use increases during flu season, and evidence indicates that the average teacher does not use sick leave for leisure, though some subsets of teachers (e.g., the young and inexperienced) do. Usage increases with leave balance; the elasticity is around 0.4. Further, teachers with higher balances are less likely to work sick, particularly during flu season.